(untitled) (Advancements in Homeopathic Research, 2025)
Introduction Worm infestation refers to the invasion of parasitic worms inside the digestive tract. Patients can be asymptomatic or exhibit long-term effects like growth retardation and malnutrition, while symptomatic patients often present with gastrointestinal disorders. Description This study evaluates the efficacy of Filix Mas, a rare remedy referenced in Boericke’s Repertory for worm symptoms, especially with constipation. The study analyzed treatment outcomes for gastrointestinal disorders due to worm infestations in children by administering Filix Mas 30 CH. Objectives • Clinical verification of Filix Mas symptoms. • Assessment of the therapeutic importance of Filix Mas for worm infestations. • Evaluation of Filix Mas’s efficacy in managing gastrointestinal disorders from parasitic worm infestations. Methods This pilot study was conducted at Dr. Madan Pratap Khuteta Homoeopathic Medical College, Jaipur, for 6 months. the study included 35 pediatric patients with confirmed worm infestations via the Stool Ova & Parasite Test. Factors such as age, sex, area, hygiene, and helminth type were analyzed. Treatment followed Hahnemannian Guidelines, with outcomes measured using the Visual Analogue Scale (VAS) and post-treatment O&P Test. Results Worm infestations were most common in children aged 7-9 years, particularly in males and those from rural areas with poor hygiene. Ascaris lumbricoides was the most frequently diagnosed helminth. Among the 35 patients, 8 (22.85%) showed markedimprovement, 19 (54.28%) moderate improvement, 6 (17.14%) mild improvement, and 2 (5.71%) no change. Statistical analysis (Paired t-test) confirmed significant improvement, with a 95% confidence interval for the difference ranging from 2.62161 to 4.06410, rejecting the null hypothesis. Conclusion Filix Mas proved effectiveness in treating gastrointestinal disorders from worm infestations, with most patients showing significant improvement. Further research with larger samples and diverse populations is recommended. The study’s limitations include its short duration and small sample size